2009
DOI: 10.1038/mp.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

The importance of irritability as a symptom of major depressive disorder: results from the National Comorbidity Survey Replication

Abstract: Irritability is a diagnostic symptom of child-adolescent but not adult major depressive disorder (MDD) in both the DSM-IV and ICD-10 systems. We explore the importance of irritability for sub-typing adult DSM-IV MDD in the National Comorbidity Survey Replication (NCS-R), a national US adult household survey. The WHO Composite International Diagnostic Interview (CIDI) was used to assess prevalence of many DSM-IV disorders in the lifetime and in the year before interview (12-month prevalence). MDD was assessed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
157
3
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(194 citation statements)
references
References 33 publications
20
157
3
14
Order By: Relevance
“…6,11,13,14 It is not clear why the magnitude of the lurasidone treatment effect observed in the current study was larger among patients with irritable features. Larger MADRS effect sizes appeared to be attributable, in part, to reduced improvement on placebo among patients with (vs. without) irritability (MADRS change = -9.5 vs. -13.8, respectively), while improvement on lurasidone was somewhat higher among patients with (vs. without) irritability (MADRS change = -22.6 vs. -19.9, respectively).…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…6,11,13,14 It is not clear why the magnitude of the lurasidone treatment effect observed in the current study was larger among patients with irritable features. Larger MADRS effect sizes appeared to be attributable, in part, to reduced improvement on placebo among patients with (vs. without) irritability (MADRS change = -9.5 vs. -13.8, respectively), while improvement on lurasidone was somewhat higher among patients with (vs. without) irritability (MADRS change = -22.6 vs. -19.9, respectively).…”
Section: Discussioncontrasting
confidence: 58%
“…8,17,20,21,34,35 The presence of irritability complicates the clinical picture of MDD with mixed features and may further increase treatment resistance to standard antidepressants. 6,[11][12][13][14][15] In the first prospective placebo-controlled trial in MDD with subthreshold hypomania (mixed features), lurasidone demonstrated significant efficacy in improving the symptoms of depression and subthreshold hypomanic symptoms. 29 The post-hoc analysis reported here now extends these results by finding lurasidone to have significant efficacy in MDD with mixed features patients who also presented with irritability (defined by the attainment of threshold scores on two irritability-related YMRS items).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations